Nutrient Intake according to Weight Gain during Pregnancy, Job Status, and Household Income - Jung, You-Mi (Clin Nutr Res, 2017)
The objective of this study was to investigate the association of nutrient intake and pregnancy outcome mediated by weight gain during pregnancy, job status, and household income. Maternal age, educational level, self-reported pre-pregnancy weights, educational level, and household income were collected from the women at 2 months postpartum. For each offspring, weight at birth, length at birth, and gestational age were collected. Participants were asked to report the frequency of consumption of foods between 28–42 weeks into the pregnancy. Diet was assessed by using a validated 106-item semi-quantitative food-frequency questionnaire (SQFFQ) and women were asked portions and quantities based on pictures, food models, and measuring tools such as cups or teaspoons. Results showed that women who gained below the recommended weight gain during pregnancy, within, and over were 25.3%, 38.7%, 36.0%, respectively. In comparison to weight gain and the offspring's length and weight at birth, the offspring of mothers with a lower weight gain had a higher length. Energy, protein, vitamin B(2), vitamin C, calcium, and potassium were significantly lower at employed group. We did not observe a significant difference between birth characteristics and maternal nutrient intake by income. Infants with a higher ponderal index at birth were born to women with a higher pre-pregnancy body mass index (BMI).